DAMPAK PERATURAN GUBERNUR ACEH NOMOR 451.2/474/2003 TERHADAP PENINGKATAN KUALITAS PENDIDIKAN DAYAH - Arfiansyah Arfiansyah; Muhammad Riza (Universitas Islam Negeri Ar-Raniry, 2016)
Dayah is an Islamic educational institutions located in Aceh. This educational institution is similar to the so-called pesantren - an Islamic boarding school in the island of Java, both from the aspect of function and purpose (although there are also some important differences). In 2003, the Government of Aceh through the Governor of Nanggroe Aceh Darussalam Decree, issued a regulation, numbered 451.2 / 474/2003 on the Criteria Stipulation and Dayah Assistance in the province of Nanggroe Aceh Darussalam (NAD). One of the subject matter is to make a policy that dayah is divided into several classifications: Type A, Type B, Type C and Non Type. This classification aims to distinguish the type of assistance to be given to dayah. This qualitative study is conducted to see how effective is the government assistance to support the quality of education in dayah. By conducting interviews to four (4) different dayah (2 interviews at traditional dayah and 2 at modern dayah), this research is expected to analyze the management of education and the impact of government assistance. The results of this study concluded that the education management of dayah remain dependent on their leadership figure (teungku), so that the impact of government assistance also varies positively to dayah physical development and improvement of facilities and infrastructure, but this assistance has also interestingly changed teungku's positive paradigm into a much more negative one.